2019
DOI: 10.1111/vsu.13287
|View full text |Cite
|
Sign up to set email alerts
|

Utility of bronchoscopy combined with surgery in the treatment and outcomes of dogs with intrathoracic disease secondary to plant awn migration

Abstract: Objective To evaluate the diagnostic and therapeutic utility of bronchoscopy in dogs undergoing computed tomography (CT) and surgery for intrathoracic disease (pyothorax and pneumothorax) secondary to migrating plant awns (MPA) and to report outcomes in dogs that did and did not undergo bronchoscopy in addition to CT and surgery. Study design Retrospective case series. Animals Thirty‐seven client‐owned dogs. Methods Medical records from 2008 to 2017 were reviewed for dogs with documented MPA in the thoracic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…One study reported a mortality rate of 6% and major delayed complications (lung lobe torsion, pulmonary aspergillosis and pneumonia) in 12% of dogs with intrathoracic grass awn. 28 No such complications were seen in the present study but pyothorax cases were not included, and pneumectomies were not indicated.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…One study reported a mortality rate of 6% and major delayed complications (lung lobe torsion, pulmonary aspergillosis and pneumonia) in 12% of dogs with intrathoracic grass awn. 28 No such complications were seen in the present study but pyothorax cases were not included, and pneumectomies were not indicated.…”
Section: Discussionmentioning
confidence: 62%
“…In a recent study, a conversion to sternotomy was observed in only three cases on 37 dogs with thoracic plant migration. Two dogs had a conversion after thoracoscopy and one dog after intercostal thoracotomy 28 . None of our cases necessitated conversion to sternotomy to find the perforated lobe.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations